DESCRIPTION OF MOTHER'S KNOWLEDGE ABOUT STIMULATION IN CHILDREN AGED 3-6 YEARS WHO ARE GIVEN BRAIN GYM AT HARAPAN BANGSA PLAYGROUPS AND MASYITHOH KAUMAN KINDERGARTEN BANTUL - Antika Indah Ariyani; Lia Dian Ayuningrum; Restu Pangastuti (Jurnal Smart Kebidanan, 2024)
Stimulation can excite brain cells and is crucial for enhancing a child's sensory, emotional, social, linguistic, cognitive, independent, and creative abilities. For the proper development of their behavioral and mental health, children must also receive enough stimulation from an early age, in both quantity and quality. Youngsters who grow up with lots of encouragement will mature more quickly than those who don't. Parents can stimulate their child's growth in a fun way, such as by participating in brain gym. This study was to find out the description of mothers' knowledge about stimulation for children aged 3rd-6th years who were given brain gym. This type of research is quantitative cross sectional with the sample at Harapan Bangsa playgropus and Masyithoh Kauman Kindergarten was 106 mother of students. It was known that the age of the majority of respondents was between 25th–35th,most of their was senior high school, income was minimum wage, most of respondents cared for themselves and time spent with children per day was > 12hours. The majority of respondents had good knowledge. This study suggests that parents—particularly mothers—should provide their children more stimulation through Brain Gym in order to enhance their development.